Using English Movie as an Attractive Strategy to Teach Senior High School Students English as A Foreign Language - Kusumaningrum, Maria Asumpta Deny (LLT Journal: A Journal on Language and Language Teaching, 2015)
The major purpose of this paper is to reveal how to implement English movies in teaching English as foreign Language to senior high school students. English as Foreign Language is implemented as the compulsory subject to learn in senior high school in Indonesia. Unfortunately, beyond the implementation, the fact that not all pupils enjoy learning English occurs. Realizing that fact, teachershould find a strategy to attract students attention to learn EFL. Moreover, using English movies to teach English can be the answer. In the application, teacher can use English movies to teach four skills. They include listening, speaking, and also writing skills. By using English movies, teacher can also teach grammar and introduce new vocabulary to students. Furthermore, the belief that everyone loves watching movies strengthens the teachers confidence to use English movies as an attractive strategy to teach English as a Foreign Language to senior high school students.